GELATIN-BASED COLD COMPRESS PATCHES INFUSED WITH AROMATHERAPY: A NOVEL APPROACH FOR MANAGING TREMOR SYNDROME, ANXIETY, AND SLEEP QUALITY - Raisa, Neila; Harbiyanti , Novita Titis; Dewi, Elvira Sari; Pratiwi , Ardine Cahya (MNJ (Malang Neurology Journal), 2026)
Background: Tremor syndrome is a common movement disorder that can impair daily function and quality of life. It is often accompanied by anxiety and sleep disturbances, which may not respond optimally to pharmacological treatment. Combining cold compress therapy with aromatherapy in a gelatin-based patch may offer a novel complementary approach. Objective: This study aimed to assess the efficacy of gelatin-based aromatherapy cold patches in recing tremor severity, improving sleep quality, and alleviating anxiety in individuals with tremor syndrome. Methods: The experimental study involved 28 participants diagnosed with tremor syndrome, divided into two treatment groups. Baseline assessments included the Archimedes scale for tremor severity, the Generalized Anxiety Disorder-7 (GAD-7) for anxiety, and the Pittsburgh Sleep Quality Index (PSQI) for sleep quality. Participant received a daily gelatin-based cold compress patches infused with aromatherapy for or two consecutive days. Post-treatment assessments were conducted to evaluate changes. Results: The application of gelatin-based cold compress patches infused with aromatherapy significantly reduced tremor severity, with pre-treatment scores of 22.38 ± 2.14 (Group 1) and 21.73 ± 1.53 (Group 2), and post-treatment scores of 21.23 ± 1.88 (Group 1) and 20.27 ± 2.52 (Group 2),  p-values of 0.005 for Group 1 and 0.017 for Group 2. However, no significant changes were observed in anxiety or sleep quality (p-values of 0.268 and 0.084 for anxiety, and 0.082 and 0.164 for sleep quality in Groups 1 and 2, respectively). Conclusion: Gelatin-based cold compress patches infused with aromatherapy may serve as an effective complementary treatment in reducing tremor severity in individuals with tremor syndrome.